NEGOTIATING HYBRID IDENTITY: THE MUHAMMAD CHENG HOO MOSQUE AND CHINESE MUSLIM COMMUNITY INTEGRATION IN BERASTAGI - Artanti, Nabilah Aprilia; Ismail, Ismail; Muary, Rholand (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study examines how the Muhammad Cheng Hoo Mosque in Berastagi symbolizes Chinese Muslim identity within a predominantly non-Muslim Karo society, addressing a gap in understanding hybrid identity formation among